Load-bearing masonry system adoption and performance: A case study of construction company in a developing country - Ramli, Nor Azlinda; Abdullah, Che Sobry; Mohd Nawi, Mohd Nasrun; Bahaudin, Ahmad Yusni (2016)
This study addresses the factors that influence the adoption of load-bearing masonry (LBM) system. A case study of the load-bearing masonry (LBM) system adoption is conducted through an interview to explore the situation of the technology adoption in a construction company.The finding indicates the factors influence the adoption of LBM system for the construction company are: organizational resources, usefulness, less maintenance, reduce construction time and cost.From the findings, these factors consistent with previous literature. Furthermore, the performance of the company was measured by looking into the financial and non-financial aspects.The LBM system brings good performance as it increased the profits of the company, a good quality of product and attracts more demand from customers.Thus, these factors should be considered for the other companies that are interested in implementing the LBM system in their projects.